2023
DOI: 10.33546/bnj.2789
|View full text |Cite
|
Sign up to set email alerts
|

Exploring nurses’ experiences in applying AIDET framework to improve communication skills in the emergency department: A qualitative study

Werapol Panchuay,
Thassanee Soontorn,
Praneed Songwathana

Abstract: Background: Recognizing the significance of effective communication in raising emergency department service standards and preventing misinterpretation of patient needs among registered nurses is crucial for improving patient satisfaction. The utilization of the AIDET (Acknowledge, Introduce, Duration, Explanation, and Thank you) communication framework is acknowledged to enhance communication among registered nurses, patients, family members, and other healthcare professionals. Objective: This study aimed to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…It has gained traction in recent training programs worldwide (Puppala et al, 2020 ). Studies, particularly in Thailand, have demonstrated the potential of AIDET to enhance patients’ experience and care delivery (Panchuay et al, 2023 ; Thangkratok et al, 2017 ). This easy-to-remember approach significantly improves interactions between patients and healthcare providers (Dhir, 2022 ; Kourkouta & Papathanasiou, 2014 ; Meehan, 2021 ; ODaniel & Rosenstein, 2008 ; Turner et al, 2016 ; Yang & Kim, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has gained traction in recent training programs worldwide (Puppala et al, 2020 ). Studies, particularly in Thailand, have demonstrated the potential of AIDET to enhance patients’ experience and care delivery (Panchuay et al, 2023 ; Thangkratok et al, 2017 ). This easy-to-remember approach significantly improves interactions between patients and healthcare providers (Dhir, 2022 ; Kourkouta & Papathanasiou, 2014 ; Meehan, 2021 ; ODaniel & Rosenstein, 2008 ; Turner et al, 2016 ; Yang & Kim, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding how communication unfolds in the Philippines is particularly relevant, especially considering the potential influence of cultural nuances on patient interactions. While adaptations of the AIDET framework have been explored in Thailand (Panchuay et al, 2023 ), a gap remains in understanding how Filipino nurses and student nurses utilize this framework in their daily practice.…”
Section: Introductionmentioning
confidence: 99%